2011
DOI: 10.1108/09574091111181336
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model assessment of logistics strategy

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…Although some of the reliability scores were below the suggested levels in the literature, in general we can make a case that these scores are satisfactory for testing and validating the structure reported in Kohn, McGinnis, and Kara (2011). In addition, as coefficient values are relatively receptive to the number of items in the constructs, particularly when constructs have .000 .000 *Scale Scores = (Sum of item scores of items in that scale) / (Number of items) **Scales: 1 = Strongly Agree, 2 = Agree, 3 = Neither Agree nor Disagree, 4 = Disagree, 5 = Strongly Disagree.…”
Section: 440mentioning
confidence: 59%
See 1 more Smart Citation
“…Although some of the reliability scores were below the suggested levels in the literature, in general we can make a case that these scores are satisfactory for testing and validating the structure reported in Kohn, McGinnis, and Kara (2011). In addition, as coefficient values are relatively receptive to the number of items in the constructs, particularly when constructs have .000 .000 *Scale Scores = (Sum of item scores of items in that scale) / (Number of items) **Scales: 1 = Strongly Agree, 2 = Agree, 3 = Neither Agree nor Disagree, 4 = Disagree, 5 = Strongly Disagree.…”
Section: 440mentioning
confidence: 59%
“…They also concluded that the six strategies (PROCSTR, MKTGSTR, INFOSTR, LCE, CSE, and COMP) had been replicated, appear to fit the construct name, and have adequate levels of reliability for further research into logistics/supply chain management. • Kohn, McGinnis, and Kara (2011) applied confirmatory factor analysis and structural equation modeling to assess logistics strategy and its relation to logistics strategy outcomes. They found that PROCSTR, MKTGSTR, and INFOSTR comprise Overall Logistics Strategy (OLS), and to the extent that LCE is effective and CSE is clear, then OLS would contribute to COMP.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Therefore, to contrast H1 we used the structural equation modelling (SEM) to ensure the relationship among capabilities and creation of value. Recent studies related with the relational capabilities and the logistic strategy have applied the SEM to contrast their hypothesis (Lado et al, 2011;Kohn et al, 2011). To validate H2 a cluster analysis was carried out in order to classify the activities in core and non-core competences, using the score of the factors obtained in the confirmatory analysis.…”
Section: Activities Of the Order Fulfillment Processmentioning
confidence: 99%
“…Modification indices (MI) are often used to assess the overall model fit (Moss, 2009). Common fit indices are RMSEA, CMIN/DF, CFI, and IFI (Kohn et al, 2011). The value of RMSEA of 0.1 or less, CMIN/DF of less than two, and CFI and IFI of 0.80 or more represent the model as a good fit (Browne and Cudeck, 1993;Garson, 2006).…”
Section: Structural Equation Modelingmentioning
confidence: 99%